Perancangan Algoritma Komputasi Heat Exchanger Network (HEN) - Arini Puspita Ramadhanti; Zuchra Helwani; Hari Rionaldo (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Heat integration is a method used to increase energy efficiency in a circuit that process with utilizing the energy potential of other process units. The utilization of the energy potential ofother process units can be done with the installation of the Heat Exchanger Network (HEN) which aims to save usage utility either steam or cooling water, so that the production cost can beminimized. Design HEN need analysis, start from the analysis of the minimum energy efficient in a network that is calculate the Maximum Energy Recovery (MER) targets, design heat exchanger network system that is network design. In this research, the MER calculation using the temperature interval and network design using the pinch method. Goals at this research is to generate algorithm computation and tools computation for design HEN. Algorithm computation of MER calculation with temperature interval method consist of input, problem tablecomputation, cascade diagram computation and output. Algorithm computation of network design with pinch method consist of identification the flow on hot side and cold side, identification sream matching at hot side and cold side, calculation of heat (Q) of heat exchangers, analysis heat (Q) of heat exchanger, and analysis hot utility ( H Q ), cold utility, and(QC ) dan T . At MER calculation was obtained minimum hot utility ( hmin Q ), minimum cold utility ( cmin Q ), and pinch temperature ( pinch T ). Sythesis HEN was displayed in Grid Diagram. Design algorithm of computation was simulated by Java programming that is displayed by Graphical User Interface (GUI).Kata kunci : heat integration, Heat Exchanger Network (HEN), Maximum Energy Recovery (MER), network design, pemoraman Java.